More Like Us: How Religious Service Attendance Hinders Interracial Romance - Perry, Samuel L. (2014)
Religious service attendance is a consistently strong predictor of aversion to interracial romance, but intervening social mechanisms at work in this relationship have yet to be explicated. This article examines whether the persistent negative association between religious service attendance and interracial romance is mediated by a preference for religio-cultural endogamy—a form of cultural purity. Multivariate analyses of national-level survey data reveal that persons who believe it is more important that their romantic partner shares their particular religious understandings are less likely to have interracially dated, and that the initially strong effect of religious service attendance on interracial romance is completely mediated by the inclusion of desire for religio-cultural endogamy in regression models. I argue that, because the majority of American congregations are racially homogenous, more frequent attendance hinders interracial romantic engagement by embedding churchgoers within primarily same-race religio-cultural communities, and because congregational embeddedness influences members to seek romantic partners similar to the group, more embedded members are less likely to view different-race persons as sharing their religio-cultural understandings, and thus, as romantic options.